Enhancing dosimetric practices through knowledge-based predictive models: a case study on VMAT prostate irradiation - Hadj Henni, Ahmed; Arhoun, Ilias; Boussetta, Amine; Daou, Walid; Marque, Alexandre (Frontiers in Oncology, 2024)
Introduction: Acquisition of dosimetric knowledge by radiation therapy planners is a protracted and complex process. This study delves into the impact of empirical predictive models based on the knowledge-based planning (KBP) methodology, aimed at detecting suboptimal results and homogenizing and improving existing practices for prostate cancer. Moreover, the dosimetric effect of implementing these models into routine clinical practice was also assessed.Based on the KBP method, we analyzed 25 prostate treatment plans performed using VMAT by expert operators, aiming to correlate dose indicators with patient geometry. The 𝐷 𝑎𝑣𝑔 𝐶𝑎𝑣 (𝐺𝑦), 𝑉 45𝐺𝑦 𝐶𝑎𝑣 (𝑐𝑐), and 𝑉 15𝐺𝑦 𝐶𝑎𝑣 (𝑐𝑐) of the peritoneal cavity and the 𝑉 60𝐺𝑦 (%)and 𝑉 70𝐺𝑦 (%) of the rectum and bladder were linked to geometric characteristics such as the distance from the planning target volume (PTV) to the organs at risk (OAR), the volume of the OAR, or the overlap between the PTV and the OAR. In the second phase, the KBP was used in routine clinical practice in a prospective cohort of 25 patients and compared with the 41 patient plans calculated before implementing the tool.Results: Using linear regression, we identified strong geometric predictive factors for the peritoneal cavity, rectum, and bladder (𝑅 2 > 0.8), with an average prescribed dose of 97.8%, covering 95% of the target volume. The use of the model led to a significant dose reduction (∆)for all evaluated OARs. This trend was most notable for ∆𝑉 15𝐺𝑦 𝐶𝑎𝑣 = -171.5 cc (p = 0.003).Significant reductions were also obtained in average doses to the rectum and bladder, ∆𝐷 𝑎𝑣𝑔 𝑅𝑒𝑐𝑡 = -2.3 𝐺𝑦 (p = 0.040), and ∆𝐷 𝑎𝑣𝑔 𝑉𝑒𝑠𝑠 = -3.3 𝐺𝑦 (p = 0.039) respectively. Based on this model, we reduced the number of plans with OAR constraints above the clinical recommendations from 19% to 8%.The KBP methodology established a robust and personalized predictive model for dose estimation to organs at risk in prostate cancer. Implementing the model resulted in improved sparing of these organs. Notably, it yields a solid foundation for harmonizing dosimetric practices, alerting us to suboptimal results, and improving our knowledge.